Does Investment Literacy Reduce the Impact of Investors' Cognitive Biases While Investing? (Role of Gender Difference) - Sudirman, Wahyu Febri Ramadhan; Syaipudin, Muhammad; Hasda, Miftah; Priyatno, Arif Mudi; Mardiyah, Suci; Zahara, Alfiatun (International Journal on Social Science, Economics and Art, 2025)
This study examined the role of investment literacy in reducing cognitive biases in investment decisions, particularly availability bias, overconfidence bias, and herding bias. Using a quantitative explanatory approach, data were collected from 392 stock investors in Indonesia through surveys. The study employed Multi-Group Analysis (MGA) to assess the moderating effect of gender on the relationship between investment literacy and cognitive biases. The findings indicated that higher investment literacy significantly reduced all three biases, enabling investors to process information more objectively, assess their abilities more realistically, and make independent decisions. However, the moderating effect of gender was only significant in the relationship between investment literacy and overconfidence bias, while it had no significant impact on availability bias and herding bias. These results underscore the importance of investment literacy in minimizing irrational decision-making. The findings have practical implications for investors in improving their financial decision-making, for policymakers in designing effective financial education programs, and for academics in further developing behavioral finance research.